A Valuation Model For Assessing Compensation Arising From Oil Spills In The Niger Delta Area Of Nigeria - Kayode, Babawale Gabriel; Ukabam, Titilayo (Advances in Social Sciences Research Journal, 2018)
This study proffers an encompassing valuation model that reflects and addresses the multi-faceted, multi-dimensional and multi-disciplinary nature of the issues and activities involved in valuation for compensation for environmental contamination, particularly, oil spills. The ultimate goal of the study is overall improvement in the practice of environmental valuation in the study area in particular, and Nigeria at large. This is expected to eliminate, or at least minimize, the protracted and costly litigations, and social disquietedness often associated with assessment of compensation for oil spillage in the study area. The study is based exclusively on secondary data drawn from relevant documents including results of past studies, valuation professional standards, valuation reports, relevant statutes and case laws as well as the experience of one of the authors as expert witness in cases involving compensation for oil spills in the study area. Specifically, the study is a follow-up to Babawale (2013) which examined certain emerging issues in assessment of compensation for oil spillage in the Niger Delta area of Nigeria but came short of providing appropriate valuation model but rather recommended that further studies be carried out to fill this gap.